Probing baryogenesis with radiative beauty decay and electron electric dipole moment - Hou, Wei-Shu; Kumar, Girish; Modak, Tanmoy (Physical review, 2024)
With the Large Hadron Collider (LHC) running, we should probe electroweak baryogenesis (EWBG) while probing 𝐶⁢𝑃 violation (𝐶⁢𝑃⁢𝑉) with electron electric dipole moment (eEDM). Rooted in the flavor structure of the Standard Model (SM), the general two Higgs doublet model (g2HDM) with a second set of Yukawa couplings can deliver EWBG while surviving eEDM. We point out a chiral-enhanced top-bottom interference effect that makes 𝑏→𝑠⁢𝛾 decay an exquisite window on EWBG and eEDM, and illustrate the importance of the Δ⁢𝐴𝐶⁢𝑃 observable at Belle II.
Gesehen am 29.07.2024